(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the effect of bromelain extract on sperm quality after thawing in goats. For that, five Anglo Nubian goats, with reproductive age, clinically healthy, were used. Semen collections were performed. After concentration analysis, the total pool volume was divided into five groups. One belonging to the control group, composed of (ACP-101/102®) and four experimental groups with ACP-101/102® enriched with bromelain extract at 5% concentrations; 10%; 15% and 20%. The samples were cryopreserved with the aid of the Tk3000® device. After a period of seven days, the samples were thawed and submitted to evaluations by the CASA system. thermoresistance, fluorescent probes, comet test and ultrastructural sperm analysis test using transmission electron microscopy (TEM). In the evaluation of post-thaw sperm kinetics, it was possible to observe that the parameters of total sperm motility, the 5% bromelain group, stood out among the others, whereas in the curvilinear velocity and mean trajectory velocity the control group presented the best results. As for the integrity of sperm DNA, the concentrations of bromelain (5%, 10%, 15% and 20%) showed no significant difference in relation to the control group, demonstrating that this substance does not present genotoxicity to sperm cells. In the ultrastructural analysis, the 5% bromelain group showed the best results. In this sense, bromelain extract added to diluent media, aiming at cryopreservation, is characterized as a promising substance, especially in maintaining the integrity of sperm DNA. However, more studies are needed for its standardization.